Development of a 3-Hydroxyflavone-Loaded Gelatin–Acacia Hydrogel as a Bioactive Scaffold for Corneal Tissue Regeneration - Sundar Rajan R; Santha Sheela NB; Hosakote Sai Bhavya (The Bioscan, 2025)
Corneal injuries and degenerative disorders often result in impaired vision due to limited self-regenerative capacity and oxidative stress-induced cellular damage. The present study aimed to develop and characterize a 3-hydroxyflavone (3-HF)-loaded gelatin–acacia hydrogel as a potential bioactive scaffold for corneal tissue repair. Hydrogels were prepared by dispersing gelatin and acacia in deionized water, followed by incorporation of 3-HF (50 μg/mL) dissolved in minimal DMSO. The pH was adjusted to 6.8 to induce gelation, and formulations were stabilized for 24 hours at room temperature. The physicochemical characterization included visual assessment, pH determination, viscosity analysis, syneresis evaluation, spreadability, occlusion, and in vitro drug release studies. Compatibility between 3-HF and excipients was confirmed through FTIR analysis, indicating no chemical interactions. FESEM micrographs revealed a uniform, porous surface morphology conducive to nutrient diffusion and cell adherence. The hydrogel exhibited optimal viscosity, pH (close to physiological), and controlled drug release over six hours, ensuring sustained therapeutic delivery. Overall, the 3-HF-loaded gelatin–acacia hydrogel displayed desirable physicochemical and biological properties, suggesting its strong potential as a biocompatible and sustained-release formulation for promoting corneal wound healing and epithelial regeneration.